Theory of mind deficit in adult patients with congenital heart disease. (October 2015) - Chiavarino, Claudia; Bianchino, Claudia; Brach-Prever, Silvia; Riggi, Chiara; Palumbo, Luigi; Bara, Bruno G; Bosco, Francesca M
This article provides the first assessment of theory of mind, that is, the ability to reason about mental states, in adult patients with congenital heart disease. Patients with congenital heart disease and matched healthy controls were administered classical theory of mind tasks and a semi-structured interview which provides a multidimensional evaluation of theory of mind (Theory of Mind Assessment Scale). The patients with congenital heart disease performed worse than the controls on the Theory of Mind Assessment Scale, whereas they did as well as the control group on the classical theory-of-mind tasks. These findings provide the first evidence that adults with congenital heart disease may display specific impairments in theory of mind.